Thrombolytic Therapy Up-regulates Inflammatory Mediators Compared to Percutaneous Coronary Intervention (PCI) - Alireza Garjani; Bahram Sohrabi; Ali Akbar Movassaghpour; Sina Andalib; Mehriar Shokri; Bahar Taherkhanchi; Bahador Bagheri (Iranian Journal of Allergy, Asthma and Immunology, 2016)
The important role of reperfusion therapies in the treatment of acute myocardial infarction is well documented. However, reperfusion therapies can initiate inflammatory response and may damage the myocardium. The purpose of current study was to compare the effects of percutaneous coronary intervention and thrombolytic therapy on inflammatory markers in the setting of ST elevation myocardial infarction (STEMI). Eighty three patients with STEMI were enrolled in this study. 40 patients underwent percutaneous coronary intervention (PCI), and 43 patients received streptokinase (1.5 million IU) as a main medical reperfusion therapy. Monocyte expression of Toll-like receptor 4 (TLR4),  serum levels of TNF-α and IL-1β, red cell distribution width (RDW) and C- reactive protein (CRP) were compared between groups at admission time, two hours and four hours after termination of treatment. p<0.05 was considered as statistically significant for all tests. Compared to baseline, both treatments increased monocyte expression of TLR4, serum levels of cytokines and CRP. Compared to PCI, medical reperfusion therapy significantly raised both monocyte expression of TLR4 (39.8±4.7 % vs 49.1±3.6 %, p<0.01), and serum levels of TNF-α (13.2±3.7 pg/ml vs 25.1±2.6pg/mlp<0.05). No effect was seen on RDW levels. Moreover, medical reperfusion therapy caused significant rise in CRP levels (p<0.01). The present study demonstrates that thrombolytic therapy is associated with higher inflammatory responses compared to PCI. Our findings suggest that thrombolytic therapy may increase the likelihood of detrimental effects of reperfusion therapy on the myocardium